Symptomatic lumbar stenosis due to low-grade degenerative spondylolisthesis can effectively be treated with mere decompression - van Grafhorst, Judith M. P.; Dijkerman, Manon L.; Peul, Wilco C.; Vleggeert-Lankamp, Carmen L. A. (Acta neurochirurgica, 2023)
Purpose Adding instrumented spondylodesis to decompression in symptomatic spinal stenosis with degenerative spondylolisthesis is subject of debate. The presence of spondylolisthesis due to degeneration is an indicator of severe facet joint and intervertebral disc degeneration, and this may fit increased instability of the spine. We aim to establish the incidence of degenerative spondylolisthesis in spinal stenosis surgical candidates and to evaluate the incidence of failure of decompressive surgery without concomitant spondylodesis as initial treatment. Methods Medical files of all operated patients for spinal stenosis between 2007 and 2013 were evaluated. Demographic characteristics, pre-operative radiological characteristics (level of stenosis, presence, and grade of spondylolisthesis), surgical technique, incidence, and indication for reoperation were summarised, as well as the type of reoperation. Patient satisfaction was classified as ‘satisfied’ or ‘unsatisfied’ after initial and secondary surgery. The follow-up was 6 to 12 years. Results Nine hundred thirty-four patients were included, and 253 (27%) had a spondylolisthesis. Seventeen percent of the spondylolisthesis patients receiving decompression were reoperated versus 12% of the stenosis patients ( p =.059). Reoperation in the spondylolisthesis group concerned instrumented spondylodesis in 38 versus 10% in the stenosis group. The satisfaction percentage was comparable in the stenosis and the spondylolisthesis group two months after surgery (80 vs. 74%). Of the 253 spondylolisthesis patients, 1% initially received instrumented spondylodesis and 6% in a second operation. Conclusion Lumbar stenosis with and without (low-grade) degenerative spondylolisthesis can usually effectively be treated with mere decompression. Instrumented surgery in a second surgical procedure does not lead to less satisfaction with surgical outcomes.